Knowledge, attitude and practice of nurses towards major immobility complications and its associated factors at governmental hospitals in Addis Ababa, Ethiopia: A cross-sectional study - Meaza Asfaw; Berhanu Wordofa; Yohannes Ayalew; Teshome Habte (Elsevier, 2021)
Aim of the study: To explore nurses' knowledge, attitude, and practice of nurses' immobility complications and associated factors in selected governmental hospitals, Addis Ababa, Ethiopia. Methods: An institution-based cross-sectional study design was conducted from February to March 2020, with a total sample of 422 randomly selected nurses working in three public hospitals in Addis Ababa city administration. Data were collected using a standard questionnaire. The collected data were checked for completeness, coded, entered, and cleaned using EPI Data version 3.1 software. The entered data were exported and analyzed by using Statistical Package for Social Science (SPSS) version 24 software. Descriptive and multivariate analyses were computed to test whether there is an association between attitude and the independent variables that show P-values ≤ 0.05 with 95% confidence interval considered statistically significant factors for attitude towards professionalism. Result: The sample of the study was gathered in the three selected public hospitals with a response rate of 99.1%. This finding reveals that 296 (70.8%), 279 (66.7%) and 234(55.9%) of nurses have good knowledge, a favorable attitude and good practice of nurses towards the care of major immobility complications respectively. Nurses with previous training (adjusted Odd Ratio 3.59, 95% Confidence Interval (2.049, 6.292)), work experience of 6-10yrs adjusted odds ratio 8.214, 95% (4.555, 14.812), and work experience of above 10 years adjusted odd ratio 9.975, 95% Confidence Interval (3.484, 28.553)) correlated with attitude and the practice of nurses in major immobility complications. Conclusion: The finding of this study shows that the experience of major immobility complications of nurses' knowledge, attitude, and practice was unsatisfactory and nurses who had on job training, work experience, and age of nurses were associated with major immobility complications. Therefore, gap-filling on-job training is an important step to advance nurses' knowledge, attitude, and practice of immobility complications.